Current and future therapies for gout. (13th August 2017) - Pascart, Tristan; Richette, Pascal
ABSTRACT: Introduction : Gout is a common disease responsible for recurrent flares triggered by the deposition of monosodium urate crystals secondary to longstanding hyperuricaemia. The management of gout implies both the treatment of flares and the treatment of hyperuricaemia itself. Recent improvement in the understanding of the disease led to the development of new drugs. Areas covered : This review covers data related to 'old' treatments of flares and hyperuricaemia, evidence on the recently approved drugs and emerging therapies in development. Expert opinion : Recent data provide a good grasp of the optimal use of colchicine, corticosteroids and NSAIDs for the treatment of flares. Interleukin-1 blocking therapies have an increasing role in the management of difficult-to-treat gout. Sub-optimal use of allopurinol is common and its potency to reduce serum uric acid (SUA) levels is underestimated. Febuxostat effectively reduces SUA levels. New uricosurics, notably lesinurad and arhalofenate, in combination with xanthine oxidase inhibitors, offer promising perspectives to help a greater number of patients achieve sufficient SUA reduction.